Pengaruh Audit Internal Terhadap Pelaksanaan Good Corporate Governace PT. Perkebunan Nusantara XIV - Utami, Winda Nurtria; Masnawati, Masnawati; Fajriani, Fajriani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
As the company grows, problems and activities will become more complicated, resulting in difficulties for the company to oversee operational activities that cause unhealthy governance. This study aims to analyze the influence of internal audit on the implementation of Good Corporate Governance. This study uses quantitative research which is a research method that uses data in the form of numbers and analysis using statistics. Data collection uses survey and documentation techniques. The data analysis methods used are descriptive statistical analysis and simple linear regression analysis. The results of the study show that internal audit has a positive and significant impact on the implementation of Good Corporate Governance of PT Perkebunan Nusantara XIV. The influence of internal audit has contributed to Good Corporate Governance by 37.7% and the rest is influenced by other factors